1996
DOI: 10.1046/j.1537-2995.1996.36496226154.x
|View full text |Cite
|
Sign up to set email alerts
|

Human blood groups: incidental receptors for viruses and bacteria

Abstract: ALMOST A CENTURY AGO, the first red cell blood groups, as determined by human sera, were described. During the subsequent years, great progress was made in the recognition and grouping of relationships of various specificities. There currently are 276 discrete red cell antigens. While 61 remain to be classified, 215 of these antigens can be grouped into 23 distinct systems. In 12 of the systems there exists a null cell, which is totally devoid of any representative antigens for that system. The recognition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 109 publications
2
32
0
1
Order By: Relevance
“…Such findings are in line with the vision whereby different BGAs serve as ''incidental receptors for viruses and bacteria'' (Moulds et al 1996), but also function as modulators of innate immune response (Ruiz-Palacios et al 2003;Linden et al 2008) and possibly as ''decoy-sink'' molecules targeting pathogens to macrophages (Gagneux and Varki 1999).…”
supporting
confidence: 82%
“…Such findings are in line with the vision whereby different BGAs serve as ''incidental receptors for viruses and bacteria'' (Moulds et al 1996), but also function as modulators of innate immune response (Ruiz-Palacios et al 2003;Linden et al 2008) and possibly as ''decoy-sink'' molecules targeting pathogens to macrophages (Gagneux and Varki 1999).…”
supporting
confidence: 82%
“…Furthermore, the results showed that patients with the blood group O and Rh positive were most susceptible towards HBV and HCV infections. With the help of scientific evidence it can be correlated that the level of natural antibodies resistance against the viral antigens depends on the individual's blood group 26 and Group O individuals were more resistant to dangerous sequelae of acute viral hepatitis. 27 A disproportionate excess of blood group O was found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that this phenomenon represents an example of a balanced polymorphism in the human population because blood group O is thought to confer susceptibility to diseases such as cholera (36) and other diarrheal diseases (37-39) that may be a significant selective force in many malarious countries. The global distribution of ABO blood group types is complex and may be influenced by selection imposed by a variety of pathogenic microorganisms (40,41). Our work indicates that malaria is likely to be a significant factor influencing ABO blood group frequencies in tropical and subtropical regions of the world.…”
mentioning
confidence: 80%